(untitled) (Cardiovascular Journal, 2014)
Background: Arterial stiffness assessed noninvasively with aortic pulse wave velocity (PWV) has been associated with atherosclerosis in the coronary arteries and also cardiovascular mortality. The aim of this study was to evaluate the association between aortic PWV and severity of coronary artery disease (CAD) in patients with acute ST elevation myocardial infarction (STEMI). Methods: This cross sectional analytical study was conducted over 200 acute STEMI patients who were purposively selected and agreed to do coronary angiogram during index hospital admission. Assessment of aortic PWV was performed noninvasively with the commercially available SphygmoCor system using applanation tonometry with high fidelity micromanometer on the day before angiogram. Study subjects were subdivided into two groups on the basis of PWV. In group I: aortic PWV was d 10 m/sec and in group II: aortic PWV was> 10 m/sec. One hundred patients were included in each group. Angiographic severity of CAD was assessed by vessel score, Friesinger score and Leaman score. Results: Vessel score 0 and 1 were significantly higher in group I (p<0.05) where vessel score 2 and 3 were significantly higher in group II (p<0.05).The mean PWV in the group with normal angiographic result was 8.10±2.9 m/sec, and in patients with single vessel disease it was 11.65±3.46m/sec. In those with double and triple vessel disease the mean value of PWV was found 13.85±3.80 and 15.70±4.66 m/sec respectively. The mean value of PWV increased in proportion with the number of vessel involved by CAD and the differences were statistically significant (p=0.001).The mean value of PWV was observed 8.5±2.3 and 12.5±3.7m/sec in insignificant and significant CAD respectively using Friesinger score and the difference was statistically significant (p<0.05).There was statistically significant positive linear relation between the values of PWV and vessel score(r=.62, p=0.01), Friesinger score(r=.64, p=0.01) and Leaman score(r=.45, p=0.01). Conclusion: Aortic PWV is associated with the extent and severity of CAD. This noninvasive, cheap, radiation free method may be considered as risk stratification tool beyond other investigations. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18351 Cardiovasc. j. 2014; 6(2): 116-121